Fabrication of Nano Filler Glass Fiber Reinforced Plastic (GFRP) with Stealth effect for Fighter aircrafts in Ku band - V. Mohan Kumar, M. Manoj Kumar, Ajay Alex Murikan, R. Prabhu, K.K. Nithiyanantham (International Journal of Advanced Science and Technology, 2020)
The invention of Radar technology in the mid 1930’s is to be considered as the most important tool used in the detection of the enemy aircrafts for a country. The first such radar was found in England by Sir Robert Watson Watt in 1935 [1]. Since the invention of radar technology, many researches were done in inventing the counter measures to absorb the electromagnetic radiation emitted by radar at a given frequency. The first Radar Absorbing Material (RAM) was introduced in 1936 in Netherlands by Naamlooze Venootschap Machinerieen [2].  The RAM is used as the chief constituent in stealth technology for absorbing the micro and radio waves transmitted by the antenna at a particular wavelength. The ultimate aim of this project is to fabricate a mid-frequency microwave absorber with increased microwave absorption characteristics in Ku band (6GHz to 18GHz) and to maintain the albedo rating of 0.1 (albedo rating = total amount of energy reflected /total amount of energy absorbed). We have dispersed the Nano particles of nickel oxide and Nano particles of activated charcoal in the matrix to enhance the microwave absorption characteristics of the composite. The composite is fabricated with two different thicknesses of 3 mm and 5 mm by compression moulding and the absorption of electromagnetic radiation is studied by using PNA test setup (absorption characterization).